LICENSING CRIMINAL ACTS IN MINING LAW: AN EPISTEMOLOGICAL ERROR WITH THE CONCEPT OF PEOPLE'S MINING AREA - Wibisana, Andi Wahyu; Syamsumardian, Lisda; Maryam, Nenden Siti; Marbun, Rocky (Proceeding International Conference of Science Technology and Social Humanities, 2023)
Money laundering crimes (TPPU) are increasingly complex, crossing jurisdictional boundaries, using increasingly varied modes. ML has penetrated into various sectors, so that it can threaten the integrity and stability of the financial system and the economy, as well as endanger the foundations of social, national and state life. This study aims to describe and analyze the regulatory dimensions of policies in controlling cash and/or other payment instruments whose implementation is borne by DJBC. This research uses a type of normative legal research method with a qualitative descriptive approach. The results of the study show that DGCE's policy in supervising the carrying of cash is based on 2 (two) dimensions of different laws and regulations. First, the dimensions of prevention, monitoring and supervision of the potential of ML. Second, the dimension of the manifestation of Bank Indonesia's authority to request information and data regarding foreign exchange activities that cross national borders. The results of the study show that DGCE's policy in supervising the carrying of cash is based on 2 (two) dimensions of different laws and regulations. First, the dimensions of prevention, monitoring and supervision of the potential of ML. Second, the dimension of the manifestation of Bank Indonesia's authority to request information and data regarding foreign exchange activities that cross national borders. The DGCE's role is increasingly important and strategic in overseeing the transfer of cash and/or other payment instruments to and from the territory of the Unitary Republic of Indonesia in order to prevent and eradicate money laundering crimes.